Resettlement, Humanitarian Admission, and Family Reunion: The Intricacies of Germany's Legal Entry Regimes for Syrian Refugees. (9th March 2018) - Tometten, Christoph
ABSTRACT: Refugees from third countries may enter Germany lawfully and obtain a residence status through several programmes. In addition to its Permanent Resettlement Programme, the Federal Government launched three so-called humanitarian admission programmes for a total of 20, 000 refugees from Syria in 2013 and 2014. All Länder except Bavaria launched state-level humanitarian admission programmes for refugees from Syria, most of which aimed at relatives of Syrians and Palestinians from Syria already living in Germany. However, none of these programmes provides its beneficiaries with the same status, the same scope of protection, the same rights and guarantees as refugees recognised in the ordinary asylum procedure. Moreover, the rights and obligations of the various programmes' beneficiaries vary between one and another. This framework is therefore not an ideal model for the development of legal entry regimes.